Untangling the impact of live baitfish restrictions on recreational fishing participation in the United States - DeRooy, Victoria; Hansen, Amanda (Frontiers in Conservation Science, 2024)
In recent decades, many jurisdictions have established regulations governing the use of live baitfish in recreational fishing. Live baitfish can originate from either aquaculture farms or wild harvest. Live bait regulations are usually motivated by conservation concerns, such as the role that live baitfish play in the spread of invasive species and aquatic diseases. One barrier that may prevent policy regulation of live baitfish is the fear among policymakers that limiting the use of live baitfish could impact the general public’s interest in fishing. However, conservation policy is hindered by the fact that there is very little research on this concern. In this study, we conduct a before-after control-intervention (BACI) analysis to test whether live baitfish regulations in the United States are followed by changes in recreational fishing. Using data from the 1960s to the present day, we analyze four states that have implemented live baitfish restrictions: Maine, New York, Vermont and Colorado. We find that live baitfish restrictions do not cause a decline in the public’s participation in fishing. Our results can empower policymakers to craft evidence-based regulations on the use of live baitfish for conservation purposes while remaining confident that such policies are not likely to cause any unintended consequences on the recreational fishing community.